Basking sharks overlap with primary and secondary deep scattering layers during overwintering migration in the Northwest Atlantic Ocean - Jaida N. Elcock; Martin C. Arostegui; Laura H. McDonnell; C. Antonia Klöcker; Gregory B. Skomal; Simon R. Thorrold; Camrin D. Braun (PLoS ONE, 2026)
Long-distance migrations allow animals to exploit seasonal prey opportunities and track favorable oceanographic conditions. The basking shark ( Cetorhinus maximus ) is a large, filter-feeding elasmobranch commonly observed in temperate shelf habitats, though it is known to seasonally occupy warmer, lower-latitude regions. In the Northwest Atlantic Ocean, basking sharks migrate from summer habitats on the continental shelf of the northeastern United States and Canada to the tropical waters of the Caribbean and South America during winter. However, the functional role of these large-scale movements is poorly understood, and their overwintering behavior during migration remains enigmatic. Here, we use pop-up satellite archival transmitting (PSAT) tags to measure basking shark vertical habitat use during this migration. Based on daily summaries of time-at-depth and time-at-temperature, we find that sharks exhibited two main behaviors: shallow epipelagic occupancy on or near the continental shelf and movements throughout the mesopelagic in offshore waters. While offshore, vertical habitat use was characterized by a strong diel vertical migration (DVM) that overlapped with primary and secondary deep scattering layers, particularly in the southern Sargasso Sea. However, DVM behavior was widespread throughout the Sargasso Sea, where most tagged individuals overwintered, and continued into the Caribbean and during trans-equatorial movements. Our results suggest basking sharks likely forage throughout these large-scale migrations, rather than relying primarily on energy stores as has been suggested for other highly migratory shark species. We also suggest that basking sharks may regularly target prey biomass in a deeper, often non-migratory prey layer below the primary deep scattering layer. These findings highlight the potential ecological importance of mesopelagic prey for basking sharks during migration and contribute to growing recognition of the ecosystem services supported by deep-pelagic food webs within and beyond the primary deep scattering layer.